The Use of Affective and Cognitive Assessment on the Learning of Mirrors and Lenses through the Inquiry Laboratory Approach - Qodar, Riskan; Samsiah, Samsiah; Haryanto, Zeni (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2018)
This study aims to examine the use of affective and cognitive assesment on the learning of mirrors and lenses with inquiry laboratory approach. The research conducted by experimental design and involved 30 students of class VIII at one of secondary high school in Samarinda, Indonesia as research subjects. Quantitative data were collected using an observation sheet for affective assessment and an essay model test instrument for cognitive assessment. Affective aspects include receiving, responding, appreciating, managing, and characterizing. Cognitive aspects for the dimensions of knowledge include factual, conceptual, and procedural, while its cognitive processes include remembering, understanding, applying, and analyzing. The learning of mirrors and lenses were taught using the inquiry laboratory approach. The approach stage of inquiry laboratory includes observation, manipulation, generalization, verification, and application. The results showed a positive correlation between affective and cognitive abilities, students with high affective abilities showed high cognitive abilities too and vice versa. The findings showed that the inquiry laboratory approach helps increase the interest and motivation and helps students to understand the concepts of mirrors and lenses.